Meta-analytical insight on probiotic metabolites and inflammatory markers in diabetes - Xie, Yanpeng; Zheng, Yingkang; Jiang, Fan; Cai, Xiaojun (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionSystemic inflammation is a hallmark of diabetes mellitus and contributes to insulin resistance and disease progression. Emerging evidence suggests that gut microbiota and their metabolites, particularly short-chain fatty acids (SCFAs), play a crucial role in modulating immune responses. Probiotics and synbiotics are increasingly explored for their potential to mitigate inflammation via microbiota-targeted mechanisms. This study aims to evaluate the effects of probiotic and synbiotic supplementation on inflammatory markers and microbial metabolites in individuals with type 1 and type 2 diabetes through meta-analytical techniques.MethodsA total of 46 randomized controlled trials (RCTs) comprising 3,580 diabetic patients were included following PRISMA guidelines. Meta-analyses were performed using random-effects models to assess changes in inflammatory markers (CRP, IL-6, TNF-α, IL-10) and SCFA levels (butyrate, propionate, acetate). Subgroup analyses and meta-regressions were conducted to identify effect modifiers such as intervention duration, formulation type (probiotic vs. synbiotic), and SCFA concentrations.ResultsProbiotic/synbiotic interventions led to significant reductions in CRP (SMD = –0.54), IL-6 (SMD = –0.41), and TNF-α (SMD = –0.48), along with an increase in IL-10 (SMD = +0.38). SCFA levels rose significantly, with butyrate showing the strongest effect (SMD = +0.46). Meta-regression revealed that butyrate levels, synbiotic use, and intervention duration ≥8 weeks were strong predictors of anti-inflammatory efficacy. Multi-strain and synbiotic interventions were more effective than single-strain or probiotic-only formulations. Sensitivity analyses confirmed the robustness of findings, and publication bias was minimal.DiscussionThese findings support the adjunctive use of targeted, SCFA-oriented probiotic formulations (e.g., Lactobacillus plantarum, Lactobacillus casei, Bifidobacterium longum with inulin/FOS, ≥10^9–10^10 CFU/day) to mitigate metabolic inflammation alongside standard care. Strain- and dose-standardized RCTs should confirm impacts on glycemic and cardiometabolic outcomes.